Ciptakan Pemilih Pemula Berkualitas Melalui Sosialisasi Terkait Pemilu Di Sman 03 Singingi Hilir - Susda Heleni; Zaitun; Nadia; Fajri Mandala Putra; Noval Devanda; Amirul Mukminin; Muthia Ramadani; Finta Kurnia; Nadila Putri Adtika; Zaiyani Ardareka; Destri Pajrya (KALANDRA Jurnal Pengabdian Kepada Masyarakat, 2023)
A number of surveys show the millennial generation and generation Z are predicted to be voter groups With the largest proportion in the 2024 Election. In the 2024 Simultaneous Election, it is predicted that the number of young voters Will have an increase. If you look at the 2019 Simultaneous Election, data from the KPU RI website The number of young voters has reached 70-80 million people out of 193 million voters. This means 35 percent up to 40 percent of young voters already have power and have a big influence on participation Election later. Based on PKPU No.7 of 2022 which states that a 17-year-old Indonesian citizen has been able to exercise his right to vote, therefore he is called a novice voter. Novice voters are those who have never used their voting rights in an election and will exercise their voting rights for the first time. Thus, this socialization is a step that Effective for creating quality elections with increased public participation Which is optimal especially from beginner voters. In this context, doing socialization is A form of movement to provide knowledge related to future elections and Provide information related to how to choose the right and right. In addition, there is also This socialization also moves novice voters to open their eyes to the nation's democracy.